One-pot synthesis of polysaccharide/gelatin amorphous hydrogels impregnated with a bioflavonoid derived from Elaeis guineensis leaf: wound healing and drug release properties - Che Zain, Mohamad Shazeli; Danish, Mohammed; Shaari, Khozirah; Fakurazi, Sharida (Springer, 2024)
Background: Amorphous hydrogel is a strategic wound healing dressings that comprised of water, polymers and excipients with no shape. The dense cross-linked network of polymer is interspersed by the immobilized water component could rehydrate and promote healing in wound tissue. Objective: In this work, various polysaccharide/gelatin amorphous hydrogels with the impregnation of oil palm leaf derived total flavonoid enriched extract (OPL-TFEE) were fabricated via one-pot synthesis method to provide multiple crosslinking networks. Method: The bioflavonoids (OPL-TFEE) were derived from Elaeis guineensis leaf using an integrated green extraction and enrichment process. Amorphous hydrogels with good wound healing properties were developed by incorporating 0.3% antioxidant agent into the hybrid polymeric gelling system. Result: The formulations appeared as a semi-solid dark yellow translucent hydrogel with good spreading and consistency characteristics and satisfying aesthetic properties. The FTIR analysis indicated that the bioflavonoid was compatible with the matrix, and the hydrogels showed porous morphological structures when observed under SEM. Furthermore, the hydrogels possessed shear thinning, pseudoplastic, and elastic properties. Bioflavonoids-impregnated polysaccharide/gelatin hydrogel release 95–98% bioflavonoids within 24 h, while the drug release profile followed the Korsmeyer-Peppas kinetic model. The hydrogels showed antioxidant and wound healing properties with no sign of cytotoxicity. Conclusion: Overall, the results revealed bioflavonoid-loaded hydrogels exhibited good physicochemical and biological properties, thus could serve as new innovative formulation in the sustainable advancement of wound care product for promoting wound healing.